The influence of deceit on the validity of a legal act (can. 125 § 2 CIC) - DZIERŻON, GINTER (Prawo Kanoniczne, 2017)
A hypothesis presented in can. 125 § 2 CIC concerning the impact of deceit on the validity of a legal act became the focus of attention of the author of the presented article. His analyses showed that out of all kinds of deceit only accidental deceit has legal effect described in can. 125 § 2 CIC. This is because for the injured party involved this form does not cause a substantial but an accidental error which does not limit the liberty of an individual to an extent which would result in the invalidity of an act. According to the author, the general rule codified in can. 125 § 2 CL is of great importance not only for theoretical-legal reasons but also because of the aspect of protection of the rights of an individual person. The legislator made it possible to rescind a valid legal act with a view to securing the rights of the injured party.